Postclassical narratology: approaches and analyses - Alber, Jan; Fludernik, Monika (Theory and interpretation of narrative, 2010)
Person, level, voice : a rhetorical reconsideration / Richard Walsh -- Mise en cadre : a neglected counterpart to mise en abyme. A frame-theoretical and intermedial complement to classical narratology / Werner Wolf -- Large intermental units in Middlemarch / Alan Palmer -- Mediacy, mediation, and focalization : the squaring of terminological circles / Monika Fludernik -- Directions in cognitive narratology : triangulating stories, media, and the mind / David Herman -- Hypothetical intentionalism : cinematic narration reconsidered / Jan Alber -- Sapphic dialogics : historical narratology and the sexuality of form / Susan S. Lanser -- Narrators, narratees, and mimetic desire / Amit Marcus -- Narratology and the social sciences / Jarmila Mildorf -- Postclassical narratology and the theory of autobiography / Martin Löschnigg -- Natural authors, unnatural narration / Henrik Skov Nielsen